Kajian Sistematis Peran Senyawa Bioaktif Fenolik Daun Salam (Syzygium polyanthum) terhadap Aktivitas Kesehatan - Rifky Rifaldo Munthe; Ardi Mustakim (CV. Muara Edukasi, 2026)
Bay leaf (Syzygium polyanthum) is a herbal plant traditionally used as a culinary ingredient and natural medicine for maintaining health. The increasing use of natural products highlights the need for a systematic scientific review to evaluate the pharmacological potential of bay leaves based on their bioactive compounds, particularly phenolic compounds. This study aims to identify the presence of phenolic compounds in S. polyanthum leaves and analyze their association with pharmacological potential in the health sector. The method involved a systematic review of relevant national and international scientific literature, selection of articles based on inclusion and exclusion criteria, and descriptive analysis of selected studies. The identification of phenolic compounds in bay leaves was conducted using a qualitative ferric chloride (FeCl₃) 3% test as the primary method. The results indicate that bay leaves are positive for phenolic compounds, as evidenced by characteristic color changes in the FeCl₃ test. These compounds contribute to various pharmacological activities, including antioxidant, antidiabetic, anti-inflammatory, and antimicrobial effects. The findings suggest that S. polyanthum leaves have potential to be developed as functional natural ingredients and phytopharmaceutical candidates, although further studies on quantification and method standardization are required.